2013
DOI: 10.5812/aapm.9653
|View full text |Cite
|
Sign up to set email alerts
|

Conscious Sedation and Analgesia in Colonoscopy: Ketamine/Propofol Combination has Superior Patient Satisfaction Versus Fentanyl/Propofol

Abstract: BackgroundColonoscopy is performed without preparing sedation in many countries. However, according to the current literature patients are more satisfied when appropriate sedation is prepared for them.ObjectivesWe hypothesize that propofol-ketamine may prepare more patient satisfaction compared to propofol-fentanyl combination.Patients and MethodsSixty adult patients older than 18 with ASA physical status of I, II or III were enrolled in the present study after providing the informed consent. They were prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 24 publications
(23 reference statements)
1
22
1
5
Order By: Relevance
“…Contradicting our findings Ghadami et al reported longer recovery duration with propofol in a group of 60 pediatric patients [18]. Khajavi et al reported similar recovery durations for ketamine-propofol and fentanyl-propofol in colonoscopy patients [19]. We believe that these differences might be secondary to study population characteristics.…”
Section: Discussioncontrasting
confidence: 64%
“…Contradicting our findings Ghadami et al reported longer recovery duration with propofol in a group of 60 pediatric patients [18]. Khajavi et al reported similar recovery durations for ketamine-propofol and fentanyl-propofol in colonoscopy patients [19]. We believe that these differences might be secondary to study population characteristics.…”
Section: Discussioncontrasting
confidence: 64%
“…However, the patient's satisfaction in the ketofol group was relatively greater than in the propofol alone group. The previous studies also confirmed that the combination of propofol and ketamine could produce more patients' satisfaction than the other regimens during colonoscopy [12] . The data regarding the safety of the combination of propofol and ketamine as well as the propofol alone for colonoscopy are limited, and there are no large prospective studies that report the safety.…”
Section: Discussionsupporting
confidence: 54%
“…It crosses the blood-brain barrier rapidly and ensures good analgesia while maintaining airway patency, ventilation, and cardiovascular stability [21]. Nevertheless, ketamine was used only in 2 earlier studies for premedication and in a recent study in combination with propofol in adult colonoscopy [22][23][24].…”
Section: Introductionmentioning
confidence: 99%